Assertive Act Found in Desmond Doss’s Conversation on “Hacksaw Ridge” Movie by Mel Gibson - Ambalegin Ambalegin; Aditya Pratama Ramadhan (Humanitatis : Journal of Language and Literature, 2022)
This research discussed the use of assertive illocutionary acts uttered by the main characters in Hacksaw Ridge movie by Mel Gibson. The data was taken from the utterances of the main character Dessmond Doss which contained assertive acts. The utterances were analyzed with the theory proposed by Searle to identify the types of assertive acts. This research was descriptive qualitative. To collect the data, the observational and non-participatory method was applied. The data collected was analyzed with pragmatic identity method and pragmatic competence- in equalizing technique proposed by Sudaryanto. In the research result, It showed that there were 28 utterances of assertive acts uttered by Dessmond Doss in Hacksaw Ridge movie. The data were found 1 data for asserting, 11 data for reporting, 4 data for complaining, 1 data for suggesting, 2 data for boasting, 2 data for explaining, and 7 data for denying. The type of reporting became the most uttered by the main character to the other character in the Hacksaw Ridge movie. It because the main character was a soldier and the event took in the battlefield where the war happened.